MENINGKATKAN KEMAMPUAN BERBAHASA LISAN ANAK USIA 5-6 TAHUN MELALUI MEDIA MAGIC BOX - Asyila Syifa, Hasna; Nopriansyah, Untung; Nopriansyaah, Untung (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2026)
This study aimed to improve the oral language skills of children aged 5–6 years through the use of magic box media at TK Assalam 1 Sukarame Bandar Lampung. The method used was Classroom Action Research (CAR) based on the Kemmis and McTaggart model, conducted in two cycles. Cycle I consisted of four meetings, while Cycle II consisted of three meetings. The research subjects were 20 children consisting of 7 boys and 13 girls. Data collection techniques use observation, interviews, and documentation, while data analysis is done qualitative. The results of the pre-research average achievement of indicators are in the category of Starting to Develop (MB) with a percentage of 85%. Based on the results of the study, it shows that there is an increase in children's oral language skills after the introduction of magic box media.. The magic box media was effective in improving the oral language skills of Group B children at TK Assalam 1 Sukarame Bandar Lampung. The percentage of children in the Very Well Developed (BSB) category increased to 85% in Cycle II and exceeded the predetermined success indicator of ≥75%.